Du caboclo à l’indigène : réflexions sur l’ethnogenèse au Brésil - Florent Kohler (Journal de la Société des Américanistes)
From caboclo to native: reflections on ethnogenesis in Brazil. Practices and representations of caboclo populations from North and Northeast Brazil display significant homogeneity. I suggest that this convergence results less from common ancestral origins than from a similarity in the oppression that these populations suffered, specifically in the form of evangelization which brought on a form of amnesia regarding origins. Nevertheless, the ancient world survives, though now underground and invisible, much like the mythical creatures that dwell there, which are said to be « enchanted ». Yet, for over thirty years, a radical reconfiguration of the relationship that the caboclo maintain with their past has emerged. Schooling, by facilitating access to caboclo national history and its local reinterpretation, has become a driving force behind their ethnic resurgence and territorial claims. Hence the emergence, instead of that of the marginalized caboclo, of a new figure: that of « the Native ». I am therefore attempting to inscribe this phenomenon of so-called « ethnogenesis » into its broader context of general reinterpretation of the past, which goes along with the collective elaboration of a pan-Indian myth of origins.